Antigenic diversity in Haemophilus ducreyi as shown by western blot (immunoblot) analysis. - Roggen, E L (1992)
The antigenic diversity within a panel of 63 Haemophilus ducreyi isolates was examined by Western blot (immunoblot) analysis with a pool of 238 well-characterized human antisera. When a serum pool adsorbed on a mixture of Haemophilus influenzae, H. parainfluenzae, and H. parahaemolyticus was used, the immunoprofiles suggested that prominent antigenic proteins involved in the human immune response have apparent molecular masses of 63, 42, 34 to 30, and 28.5 to 28 kDa. Preliminary subcellular localization revealed that these antigens are associated with the cellular membrane. Two subsets of antigens were discriminated by detergent extraction. There was no evidence that the antigen composition is altered by changing the growth conditions. With a serum pool adsorbed on the Haemophilus spp. mixture supplemented with Actinobacillus actinomycetemcomitans, Pasteurella ureae, Neisseria gonorrhoeae, and Escherichia coli, antigenic determinants more specific for H. ducreyi were identified. An immunodominant 28.5- to 28-kDa protein was expressed by all H. ducreyi isolates. In the range from 34 to 30 kDa, 56 isolates revealed a dominant protein with variable molecular mass. By using both proteins (28.5 to 28 kDa and 34 to 30 kDa) as immunotypic markers, seven different immunopatterns were identified. Antigenic diversity among isolates from different geographical origins as well as from a single area was observed.